The role of equivalence in the creation of terminology in Tshivenda : A case of the National Curriculum Statement in grades R-9 (2002) - Nefale, Shumani Joyce (My University, 2009)
A critical analysis of the Revised National Curriculum Statement Grades R-9 (2002) and the Tshitatamennde tsho Sedzuluswaho tsha Kharikhulamu Gireidi R-9 (2002) has revealed that the role of equivalence in translation cannot be taken for granted. In the study, various types of translation equivalence, such as connotative, textual, dynamic and formal, are examined. The examination reveals that formal equivalence is the type of equivalence in which the source text has a corresponding word in the target language, whereas the dynamic equivalence occasionally translates texts out of context because it does not take into account the context of the text. The study also deals with translation methods such as word–for-word, idiomatic, semantic, and communicative. The role of equivalence in their use is examined. The study also reveals that some methods are not suitable because they distort the meaning, depending on the context of the text. The communicative method has been found to be the most suitable method in translation because it is the kind of method that fulfills the purpose of translation, which is communicative equivalence.This study also highlights the issue of technical translation in aspects such as assessment, learning areas, learning outcomes, and assessment standards. The analysis reveals that the translation of a technical term by another technical term has flaws, some of them are, namely, ambiguity and the distortion of information. The study also reveals that a technical term should be translated by a descriptive term.
Thesis (M.A. (African languages)) --University of Limpopo, 2009
Keywords: Translation methods; National Curriculum Statement; 496.39765; Venda language; Venda language -- Grammar